Knowledge and the parental role in caring for children with heart disease - N Keawvichit; K Thajeen (Journal of Health Science and Medical Research (JHSMR), 2007)
Objective: To describe knowledge and the parental role in caring for children with heart disease and to identify the relationships between these two variables. Material and Methods: Eighty two parents of children with heart diseases were selected by purposive sampling from the Pediatric Cardio Clinic in Songklanagarind Hospital between January and March 2006. The data were collected using a questionnaire in two sections: parental knowledge and parental role in caring for children with heart diseases. The reliabilities for the questionnaire were 0.76 and 0.72 respectively. Results: The "Parental knowledge" was found to be at the moderate level whereas the "Parental role" in caring for children with heart disease was at a high level. An association between parental knowledge in prevention of complications and the parental role in caring for the sick was found (r = 0.31, p < .01). An understanding of parental knowledge and the parental role in caring for children with heart disease could be used to guide pediatric nurses to develop themselves and to guide their interactions with parents in order to prevent severe complications.